Long-term efficacy and safety of secukinumab in patients with psoriatic arthritis: 5-year (end-of-study) results from the phase 3 FUTURE 2 study - McInnes, Iain B.; Mease, Philip J.; Kivitz, Alan J.; Nash, Peter; Rahman, Proton; Rech, Jürgen; Conaghan, Philip G.; Kirkham, Bruce; Navarra, Sandra; Belsare, Ashwini D.; Delicha, Eumoprhia M.; Pricop, Luminita (The Lancet Rheumatology, 2020)
Background: Secukinumab is an interleukin-17A inhibitor used in the treatment of patients with active psoriatic arthritis. In the phase 3 FUTURE 2 trial, secukinumab showed sustained improvement in clinical outcomes over 2 years. Because scarce data exists on the long-term treatment with biological therapies in patients with psoriatic arthritis, we aimed to assess and describe the 5-year (end-of-study) results on the efficacy and safety of secukinumab 300 mg and 150 mg doses, as well as dose escalation, from the FUTURE 2 study. Methods: FUTURE 2 is a phase 3, double-blind, placebo-controlled study done at 76 centres in Asia, Australia, Canada, Europe, and the USA. Patients with active psoriatic arthritis aged 18 years or older were randomly assigned to either secukinumab (300 mg, 150 mg, or 75 mg) or placebo weekly from baseline and then every 4 weeks from week 4. Secukinumab dose was escalated from 150 mg to 300 mg and from 75 mg to 150 mg or 300 mg starting at week 128, if active signs of disease were observed in patients, on the basis of the physician's assessment, with the escalated dose maintained thereafter. We assessed key efficacy endpoints at week 260 (5 years) for secukinumab 300 mg and 150 mg, including American College of Rheumatology (ACR) and Psoriasis Area and Severity Index (PASI) responses. The safety analysis included all patients who received one or more doses of secukinumab. We report data as observed. This study is registered with ClinicalTrials.gov, NCT01752634. Findings: At randomisation, 65% of patients were naive to tumour necrosis factor inhibitors and 47% were receiving concomitant methotrexate. Of 397 patients randomly assigned in FUTURE 2, 248 (62%) completed 5 years of treatment, including 64 (64%) of 100 patients in the original secukinumab 300 mg group, 65 (65%) of 100 in the 150 mg group, 59 (60%) of 99 in the 75 mg group, and 60 (61%) of 98 in the placebo group. Overall, 127 (52%) of 242 patients required dose escalation during the study. ACR responses at 5 years were 71 (74%; ACR20), 50 (52%; ACR50), and 31 (32%; ACR70) of 96 evaluable patients in the secukinumab 300 mg group, and 67 (70%; ACR20), 41 (43%; ACR50), and 28 (29%; ACR70) of 96 evaluable patients in the secukinumab 150 mg group. From 24 to 32 weeks and from 48 to 84 weeks after dose escalation from secukinumab 150 mg to 300 mg, the proportions of ACR and PASI non-responders decreased, whereas the proportions of ACR and PASI responders increased. During the entire treatment period, the most frequent treatment-emergent serious adverse event was serious infection (exposure-adjusted incidence 1·7, 95% CI 1·1–2·5; n=25) in the any secukinumab group. No new or unexpected safety signals were reported. Interpretation: Secukinumab 300 mg and 150 mg provided sustained improvement in the signs and symptoms of psoriatic arthritis, with consistent safety over 5 years. This study supports the clinical benefit and safety of long-term treatment with secukinumab in patients with psoriatic arthritis. Funding: Novartis.
CRIS-Team Scopus Importer:2020-03-31